The Economics of Climate Change Impacts and Policy Benefits at City Scale A Conceptual Framework - Hallegatte, Stéphane (OECD Environment Working Papers, 2008)
Climate change has become a priority issue in global environmental governance and cities are important players. For over three decades, the OECD has been actively supporting member and non-member countries to design environmental policies that are both economically efficient and effective at achieving their environmental objectives.1 Through peer reviews of policy implementation, the OECD helps governments to improve their collective and individual environmental performance, through sound economic and policy analysis and dialogue on how to establish and to achieve climate change goals. Climate change has been on the agenda since the late 1980s at the OECD, where we provide a forum for countries to, discuss and develop a shared understanding of the key policy challenges as well as to assess performance and identify good practice in the design and implementation of climate policies. Today the OECD is actively working with governments to highlight the role of cities to deliver cost-effective policy responses to climate change. A number of projects at the OECD are advancing the understanding of the roles that cities can play to respond to efficiently and effectively to climate change. This report is one in a series under the OECD Environment Directorate's project on Cities and Climate Change. The project aims to explore the city-scale risks of climate change and the local benefits of both adaptation policies and (global) mitigation strategies